Analisis Implementasi Pendidikan Multikultural melalui Pendidikan Pancasila di SMP Negeri 7 Medan - Dhio Febriansyah Lubis; Ema Serika Ginting; Maria Dwi Sianipar (Lembaga Pengembangan Kinerja Dosen, 2025)
Multicultural education is an important approach in a diverse society like Indonesia, with the aim of developing human potential as a whole while respecting diversity. This education emphasizes the recognition and appreciation of cultural, ethnic, religious, and linguistic differences, and also develops an attitude of tolerance and empathy for individuals from diverse backgrounds. This study aims to determine the implementation of multicultural education in the Pancasila Education subject at SMP NEGERI 7 Medan. This study uses a qualitative method with a descriptive approach. Data collection techniques are carried out through observation, interviews, and documentation. The subjects of this study consisted of Pancasila education teachers and students at SMP NEGERI 7 Medan. The location of the study was chosen at SMP NEGERI 7 Medan because this school has implemented multicultural education that combines diversity in school life. SMP Negeri 7 Medan illustrates the abundant diversity of students, especially in the field of religion, with students from various beliefs studying together, as well as various social and cultural backgrounds. The school holds a weekly structured literacy program, which is linked to the Pancasila Student Profile Strengthening Project (P5) to develop literacy skills and reinforce Pancasila values. Religious activities are held every Friday to strengthen students' religious and ethical values, while